Drug-eluting stent use after coronary atherectomy: results from a multicentre experience – The ROTALINK I study. Issue 9 (September 2016) - Cortese, Bernardo; Aranzulla, Tiziana C.; Godino, Cosmo; Chizzola, Giuliano; Zavalloni, Dennis; Tavasci, Emanuela; De Benedictis, Mauro; Ettori, Federica; Presbitero, Patrizia; Colombo, Antonio
Abstract : Aims: Until now, there is no medium- to long-term clinical evidence of the best treatment after rotational atherectomy. Methods: From the databases of seven high-volume centres, years 2005–2010, we retrospectively analysed the long-term outcome of patients who had undergone rotational atherectomy followed by plain-balloon angioplasty or implantation of drug-eluting stent (DES) or bare metal stent (BMS). Primary endpoint was the incidence of major adverse cardiovascular events (MACE: death, myocardial infarction, target-lesion-revascularization) at longest available follow-up. Results: In this registry, we enrolled 1397 patients with 1605 lesions, followed for 28.4 ± 21 months. DES-treated patients were more frequently diabetic, had more lesions treated and received a higher number of stents. In-hospital MACEs were significantly higher in DES patients (7.6 vs. 2.6 vs. 2.9%, respectively, P  = 0.0001 for both), mainly due to a higher incidence of myocardial infarction (6.4 vs. 1.2 vs. 2.1%, P  = 0.0001). The 2-year follow-up showed a significantly lower incidence of MACE in DES patients (15.1 vs. 24.2 vs. 20.8%, P  = 0.001 for both), driven by a lower incidence of target-lesion revascularization (8 vs. 14.6 vs. 13.9%, P  = 0.002). Myocardial infarction rate was lower in the DES group as well (0.4 vs. 3.1% in BMS, P  = 0.001). At multivariate analysis, BMS implantation and balloon angioplasty were independent predictors of long-term MACE. DES implantation was associated with a lower risk of long-term myocardial infarction [hazard ratio 0.15, 95% confidence interval (95% CI) 0.04–0.67] and target-lesion revascularization (hazard ratio 0.42, 95% CI 0.21–0.82). Male sex and DES use were independent predictors of the absence of MACE. Conclusion: After rotational atherectomy, DES implantation appears to be a preferable strategy, as it is associated with lower long-term MACE, despite an unexpected increase in periprocedural myocardial infarction.